2011
DOI: 10.1017/s175173111000145x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endemic goitre areas on thyroid hormones in horses

Abstract: The aim of this study was to investigate thyroid hormone levels in horses stabled in two different locations on the island of Sicily. The study was carried out on a total of 72 clinically healthy Sanfratellano horses ranging in age from 5 to 9 years and weighing 585 6 40 kg. The results showed higher thyroxine values (P , 0.02) in horses stabled in an endemic goitre area (group II) than those observed in horses in a non-endemic area (group I). Unexpectedly, the T 4 /T 3 and the fT 4 /fT 3 rations were both low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The greatest release of T 3 and T 4 after transport could represent the final result of preferential release of T 3 from the thyroid gland and/or a probably increase of peripheral monodeiodination of T 4 , although a synchronous release of T 4 was observed. In addition, the higher increase of T 3 (56%) than that of T 4 (26%) obtained after transport confirmed that T 3 is a metabolically active hormone [14], and the moderate higher increase of fT 3 (18%) than that of fT 4 (5%) confirmed that the changes of free hormones generally followed those for total hormones changes as previously observed in Sanfratellano horses [2] and Thoroughbred foals [15].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The greatest release of T 3 and T 4 after transport could represent the final result of preferential release of T 3 from the thyroid gland and/or a probably increase of peripheral monodeiodination of T 4 , although a synchronous release of T 4 was observed. In addition, the higher increase of T 3 (56%) than that of T 4 (26%) obtained after transport confirmed that T 3 is a metabolically active hormone [14], and the moderate higher increase of fT 3 (18%) than that of fT 4 (5%) confirmed that the changes of free hormones generally followed those for total hormones changes as previously observed in Sanfratellano horses [2] and Thoroughbred foals [15].…”
Section: Discussionsupporting
confidence: 83%
“…A properly functioning thyroid gland is highly important to a horse's good health, and it gets more difficult and complex to know when the thyroid gland is in a state of dysfunction [1,2]. Thyroid function is essential for physiological reactions and adaptations during physical exercise and transport stress; therefore, the changes in free triiodothyronine (fT 3 ) were the most responsive to stressful conditions and may help to provide additional information for the assessment of transport stress in sport horses and about the positive effect extended by competition experience [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors and clinicians consider that thyroid gland dysfunction in horses could often be misdiagnosed due to a poor understanding of equine thyroid physiology and because reference intervals for thyroid hormones differ considerably among laboratories and measurement techniques (Mendoza et al 2013). In addition, thyroid hormones are important physiological indicators commonly used in studies concerning metabolic rate and general development (Medica et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Radioimmunoassay (RIA) is considered the gold standard method to determine thyroid hormone levels, because RIA exhibits high sensitivity and specificity and low detection limits [ 2 , 14 , 15 , 20 , 21 , 29 , 30 ]. Furthermore, equilibrium dialysis [ 2 ], ultrafiltration [ 31 ], enzyme immunoassay [ 3 , 23 , 33 , 34 ], chemiluminescence immunoassay [ 10 , 28 ], chemiluminescent enzyme immunoassay [ 11 ] and electrochemiluminescence immunoassay [ 10 , 39 ] are available to evaluate thyroid function in many species. Nonetheless, reference values of thyroid hormone concentrations vary substantially by measurement techniques used and laboratories performing the assays.…”
mentioning
confidence: 99%